Latitudinal variation in ecological opportunity and intraspecific competition indicates differences in niche variability and diet specialization of Arctic marine predators. Issue 6 (14th February 2016) - Yurkowski, David J.; Ferguson, Steve; Choy, Emily S.; Loseto, Lisa L.; Brown, Tanya M.; Muir, Derek C. G.; Semeniuk, Christina A. D.; Fisk, Aaron T.
Abstract: Individual specialization (IS), where individuals within populations irrespective of age, sex, and body size are either specialized or generalized in terms of resource use, has implications on ecological niches and food web structure. Niche size and degree of IS of near‐top trophic‐level marine predators have been little studied in polar regions or with latitude. We quantified the large‐scale latitudinal variation of population‐ and individual‐level niche size and IS in ringed seals ( Pusa hispida ) and beluga whales ( Delphinapterus leucas ) using stable carbon and nitrogen isotope analysis on 379 paired ringed seal liver and muscle samples and 124 paired beluga skin and muscle samples from eight locations ranging from the low to high Arctic. We characterized both within‐ and between‐individual variation in predator niche size at each location as well as accounting for spatial differences in the isotopic ranges of potential prey. Total isotopic niche width (TINW) for populations of ringed seals and beluga decreased with increasing latitude. Higher TINW values were associated with greater ecological opportunity (i.e., prey diversity) in the prey fish community which mainly consists of Capelin ( Mallotus villosus ) and Sand lance ( Ammodytes sp.) at lower latitudes and Arctic cod ( Boreogadus saida ) at high latitudes. In beluga, their dietary consistency between tissues also known as the within‐individual component (WIC) increased in a near 1:1 ratio with TINW (slope = 0.84), suggesting dietary generalization, whereas the slope (0.18) of WIC relative to TINW in ringed seals indicated a high degree of individual specialization in ringed seal populations with higher TINWs. Our findings highlight the differences in TINW and level of IS for ringed seals and beluga relative to latitude as a likely response to large‐scale spatial variation in ecological opportunity, suggesting species‐specific variation in dietary plasticity to spatial differences in prey resources and environmental conditions in a rapidly changing ecosystem. Abstract : We quantified large‐scale latitudinal variation of population‐ and individual‐level niche size and degree of individual specialization in two Arctic marine predators, ringed seals, and beluga whales, using stable isotope analysis. We report an increase in isotopic niche width with decreasing latitude as a result of increased ecological opportunity for both species, as well as species‐specific differences in individual niche variability and individual specialization with the varying levels of intraspecific competition and latitude. Our findings highlight species‐specific variation in dietary plasticity to changing resource and environmental conditions in a rapidly changing ecosystem.